The field guide to drawing & sketching animals - Pond, Tim (Tunbridge Wells Search Press, 2019)
"Artist Tim Pond's lively and engaging book fuses science with art, providing the reader with the skills, techniques and knowledge they need to create sketches of animals filled with life and movement. There are some very good books written on life drawing, yet when it comes to drawing wildlife, illustrators and artists often revert to working solely from photographs, which can leave the artwork looking lifeless and flat. In this inspirational book, artist Tim Pond shows you how to observe and draw animals in zoos, farms, wildlife parks and aquariums, teaching you some fascinating facts about the animals along the way and ultimately bringing you closer to nature. One of the challenges with sketching wildlife is that animals are constantly moving, however having some basic understanding of the biology of an animal, such as knowing that a duck has a cheek or that a cheetah can't retract its claws, can influence how you might sketch them, and results in a lively drawing that captures the form, movement and ultimately the spirit of the animal in question. Combining scientific knowledge with expert practical guidance is key to creating successful drawings of animals, and Tim's ability to convey this in a way that is both accessible and engaging makes this a unique and inspiring guide suitable for artists of all levels. Tim's book takes you on a journey of discovery that will enable you to develop the skills, techniques and knowledge you need to sketch a broad range of wildlife, encompassing mammals, reptiles, birds, fish and insects. It includes quick, gestural sketches as well as linear and tonal studies, in a variety of media - pencil, pen and ink, and watercolour. There are numerous studies comprising how to represent the different patterns of animals' coats, how to capture the plumage of an exotic bird in watercolour, and how to sketch a hippo's hooves, as well as guidance on tools, materials and basic techniques. The result is a treasure chest of fascinating facts, studies, sketches and annotated drawings that will not fail to ignite your enthusiasm for drawing animals from life." -- ONIX annotation
1
Keywords: Animals in art; Animals in art; Drawing -- Technique; Drawing -- Technique; Nonfiction